The relationship between objectification and the desire to undergo cosmetic surgery: the mediating role of intuitive eating and body image flexibility - Lăzărescu, Gianina; Vintilă, Mona (Frontiers in Nutrition, 2025)
ObjectivesSociocultural standards that emphasize idealized appearance and promote the objectification of women’s bodies have been consistently associated with negative body image outcomes and increased interest in cosmetic surgery (Fredrickson & Roberts; Calogero et al.). Constructs such as body image flexibility and intuitive eating have been discussed in the literature as psychological resources that promote well-being in body image–related contexts (Sandoz et al.; Tylka & Kroon Van Diest). However, their specific role in the relationship between objectification and cosmetic surgery interest remains underexplored. Recent evidence suggests that body image flexibility may function as a protective factor in this relationship (Huang et al.), while intuitive eating has been associated with greater psychological well-being and reduced body-related distress (Tylka and Wilcox), suggesting its potential relevance. Building on this background, the present study investigates the mediating roles of body image flexibility and intuitive eating in the relationship between body objectification and the desire to undergo cosmetic surgery for intrapersonal and social reasons, as well as the likelihood of pursuing such procedures in the future.MethodsThe sample consisted of 555 Romanian women (M = 29.61 years, SD = 13.396), who completed validated scales measuring body objectification, body image flexibility, intuitive eating, and attitudes toward cosmetic surgery. Data were analyzed using parallel mediation models, controlling for age, educational status, ethnicity, relationship status, and body mass index.FindingsThe findings indicated that body objectification was negatively associated with body image flexibility and intuitive eating. While intuitive eating did not mediate the relationship between body objectification and the desire for cosmetic surgery in any of the tested models, body image flexibility emerged as a partial mediator in the model related to social motivations and a full mediator in the model predicting future consideration of cosmetic procedures. These results are consistent with theoretical frameworks emphasizing self-perception and sociocultural context—such as self-verification and self-affirmation theories—that help explain how women’s behaviors are shaped by societal expectations and patriarchal cultural norms.Conclusion and recommendationsThe study highlights the relevance of cultural context in understanding adaptive factors that may buffer the psychological impact of objectification. The results suggest that body image flexibility may function as a protective factor in reducing the desire for cosmetic surgery. While these findings may suggest potential directions for intervention, such as promoting positive body image and intuitive eating, we emphasize that further longitudinal research is needed before such psychoeducational programs can be designed or implemented. This study contributes to the growing body of literature by shedding light on culturally specific dynamics influencing cosmetic surgery motivations.